FORMAÇÃO DE DOCENTES PARA A AVALIAÇÃO DO DESENVOLVIMENTO DE CRIANÇAS COM TRANSTORNO DO ESPECTRO AUTISTA (TEA): Construindo uma intervenção pedagógica para orientar o ensino em uma creche pública de São Luís – MA - SETÚBAL, Arteane Gomes de Sousa (2024)
This dissertation aims to investigate the actions related to the assessment of the development of children up to five years of age with Autism Spectrum Disorder (ASD), with the aim of proposing educational interventions with teachers in support of the inclusive education of children with ASD, based on the Child Development Assessment Scale, with a view to creating an electronic journal that can assist regular education teachers at a Kindergarten in the Municipal Network of São Luís - MA. This study is part of an applied research with a qualitative approach. Regarding its objectives, it is exploratory and descriptive, and regarding its procedures, it proceeds as a participant intervention type. The research site was the Kindergarten “Maria de Jesus Carvalho”, a municipal school in the Camboa neighborhood, in São Luís - MA. The teachers and the coordinator of the aforementioned school participated in the intervention research. The instruments used for data collection were questionnaires and semi-structured interviews, according to the content analysis technique, and the chosen product was an electronic magazine providing guidance on how to assess child development with children with ASD. The results obtained indicated that most teachers do not have knowledge based on child development assessment, although they have a degree in Pedagogy and a postgraduate degree. The product was detailed in the methodology section, which is an electronic journal, with the results, the evaluation of the process and the discussions about the evaluation. At the end of this research, the electronic journal, as a product and instrument, summarizes the relevance of the study, and contains the theoretical and practical contribution based on children with ASD. It is expected that this research and its results can contribute to the field of studies of Special and Inclusive Education (EEI), specifically with regard to the process of inclusion of children with ASD.